2009
DOI: 10.1371/journal.pone.0005504
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of the α2A-Adrenoceptor in Producing Inflammation and Organ Injury in a Rat Model of Sepsis

Abstract: BackgroundNorepinephrine (NE) modulates the responsiveness of macrophages to proinflammatory stimuli through the activation of adrenergic receptors (ARs). Being part of the stress response, early increases of NE in sepsis sustain adverse systemic inflammatory responses. The intestine is an important source of NE release in the early stage of cecal ligation and puncture (CLP)-induced sepsis in rats, which then stimulates TNF-α production in Kupffer cells (KCs) through the activation of the α2-AR. It is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 27 publications
1
78
1
Order By: Relevance
“…These studies demonstrated that gut is the major source of the increased circulating NE in sepsis. We have also shown that NE induced hepatocellular dysfunction in early sepsis is mediated by the activation of ·2-adrenoceptors (9) and recently we reported that the · 2a form of the receptor mRNA expression is increased in Kupffer cells in response to sepsis (10). In addition, Spengler et al (11) demonstrated that stimulation of ·2 adrenoceptors augments the production of macrophage derived TNF-·.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…These studies demonstrated that gut is the major source of the increased circulating NE in sepsis. We have also shown that NE induced hepatocellular dysfunction in early sepsis is mediated by the activation of ·2-adrenoceptors (9) and recently we reported that the · 2a form of the receptor mRNA expression is increased in Kupffer cells in response to sepsis (10). In addition, Spengler et al (11) demonstrated that stimulation of ·2 adrenoceptors augments the production of macrophage derived TNF-·.…”
Section: Introductionmentioning
confidence: 86%
“…The small intestine was exposed and a branch of the superior mesenteric vein was cannulated with a PE-10 catheter. NE at 20 μM in normal saline containing 0.1% ascorbic acid or vehicle (0.1% ascorbic acid in normal saline) was infused into the portal vein at a rate of 13 μl/min for 2 h using Harvard pump as described previously (10). Liver tissues were collected, flash frozen in liquid nitrogen and stored at -80˚C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this hypothesis, Miksa et al showed in experimental models of sepsis that an 2A -adrenocepter antagonist reduced plasma levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinine, indicative for attenuated liver and kidney injury (Miksa et al, 2009). Moreover, these authors showed that inhibition of 2A -adrenocepter activation significantly improved survival in septic animals from 45 to 75% (Miksa et al, 2009). Another pathway of neuroimmune regulation is considered to be involved in the pathogenesis of VILI and MOF as well.…”
Section: Local Versus Systemic Inflammationmentioning
confidence: 98%
“…Activation of 2-AR results in an increase in cAMP concentrations, which can modulate cytokine expression, i.e., decreasing TNF- and increasing IL-8 (Elenkov & Chrousos, 1999). However, recently was described that 2A-AR stimulation increases TNF- gene expression in Kupffer cells and plasma TNF- during sepsis (Miksa et al, 2009). Thus, through AR stimulation, locally released NE, or circulating catecholamines, affect lymphocyte traffic, circulation, and proliferation, and modulate cytokine production and the functional activity of different lymphoid cells (Elenkov et al, 2000), just as they control heart rate and other vital functions.…”
Section: Reflex Control Of Inflammation: Part I -Brain-to-immune Commmentioning
confidence: 99%